Low dose alpha interferon therapy can be effective in chronic active hepatitis C. Results of a multicentre, randomised trial. Issue 4 (April 1996) - Sánchez-Tapias, J M; Forns, X; Ampurdanés, S; Titó, L; Planas, R; Viver, J M; Acero, D; Torres, M; Mas, P; Morillas, R; Forné, M; Espinós, J; et al.
Abstract : BACKGROUND–There is some controversy concerning the efficacy of low dose alpha interferon therapy in chronic hepatitis C. AIMS–To evaluate the effectiveness of treatment with low doses of alpha interferon in chronic hepatitis C. PATIENTS–One hundred and forty one patients with anti-HCV positive chronic active hepatitis C from six hospitals were enrolled in the study. METHODS–Patients were randomised to treatment with 5 MU (group A) or 1.5 MU (group B) injections. The dose was reduced in responders from group A or increased in non-responders from group B to maintain treatment with the minimal effective dose. Patients were treated for 48 weeks and followed up for 24 additional weeks with no treatment. Normalisation of alanine aminotransferase (ALT) was used to evaluate response. RESULTS–A sustained response was seen in eight patients from group A (12%) and in 15 (21%) from group B. This difference was not statistically significant. Increasing the dose of interferon led to sustained response in only five of 58 patients (9%) from group B who did not respond to 1.5 MU injections. In contrast, 15 of 21 patients (71%) in whom ALT remained normal with 1.5 MU injections developed a sustained response. By multivariate analysis sustained response seemed associated with young age and was more frequent in patients with genotype 3 HCV infection. Sustained response was preceded by a rapid normalisation of ALT and was inversely related to the amount of alpha interferon necessary to maintain ALT at low values during treatment. CONCLUSIONS–Some patients with chronic hepatitis C are very sensitive to alpha interferon and can be successfully treated with low doses. Treatment with higher doses may be effective in a minority of patients who do not respond to low doses.